Realities of the Post-conflict Period: A Real Philosophical View of the Problem Perpetual Peace - Zeynalov, Sholat (Scholarya Demo Journal of Ruby, 2021)
Long ago, he German philosopher I. Kant considered that speaking of the great perpetual peace on earth was the unforgettable noble desire of all mankind, but this was probably impossible to achieve. The great philosopher, in its most general form, connected the essence of this problem with the militaristic policy of states. It must be admitted that some countries are still pursuing this policy (such countries include, for example, Armenia).The article is devoted to the theoretical issues of communication, dialogue, culture of dialogue, peace and security. It is noted here that the problem of peace and security is the main problem of every society, state, civilization, but in most cases, the problem is not solved in the world due to false ideological, political, national, ethnic, geographical and other interests. It is worth noting that this issue has always been relevant in the world and, presumably, will continue to be so. According to the author, there is a serious need to promote the experience of dialogue and cooperation, peace and integration in the world, which Azerbaijan is currently implementing. The article also examines the humanitarian strategy pursued by the political leadership of modern Azerbaijan before the war, during the war and in the post-war epoch, which is an invaluable platform for both world and regional peace building and cooperation. Purpose: to reflect theoretically on the opportunities and prospects that the culture of communication and dialogue can create in achieving peace, security, stability, sustainable development, coexistence and solidarity in global and regional relations; Also, to draw attention to the problem of perpetual peace, which is the wish and desire of everyone in the new system of relations in the world. Methodology: comparative analysis, empirical, scientific method, historical and analytical methods. Scientific novelty: to demonstrate the restorative effect of a dialogue and communication culture in the context of peace and security, modern development, and challenges.